A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam - Nguyen, Lien Thi Phuong; Bozdoğan, Hakan; Kumar, P. Girish; Carpenter, James M. (Zootaxa, 2018)
The genus Orientalicesa has six species, and all of them have been recorded in the Oriental region (including Indonesia, Malaysia, Phillippines, Laos, China). In this paper, the genus Orientalicesa is newly recorded from Vietnam, represented by one species O. confasciatus Tan and Carpenter. This species was mistakenly redescribed as Stenodyneriellus rangpocus Kumar, Carpenter & Kishore, 2017. A new synonym of O. confasciatus is proposed, and that species is a new record for India.